(untitled) (World Bulletin of Social Sciences, 2024)
This article discusses the functional-semantic features of informal conversation in Uzbek and English languages. The types of collocations are also explored by analyzing their use in languages of different systems and ways of translating them into English and Uzbek are examined. As a result, a definition of informal vocabulary is given based on the material being studied